A review on conductive polymers and their hybrids for flexible and wearable thermoelectric applications. (May 2021) - Prunet, G.; Pawula, F.; Fleury, G.; Cloutet, E.; Robinson, A.J.; Hadziioannou, G.; Pakdel, A.
Abstract: There is a growing demand for flexible and wearable next-generation electronic devices that must be capable of bending and stretching under mechanical deformation. In this regard, energy harvesting technologies have immensely invested in organic and polymeric semiconducting materials due to their large-area synthesis, low cost, low toxicity, high flexibility, and tunable electronic properties. For example, electrically conductive π-conjugated polymers have been investigated in various thermoelectric technologies for producing stretchable, wearable, and light-weight thermoelectric devices that can harvest energy from a temperature gradient and produce electricity with no pollution or moving parts. In this review we initially provide a general overview of the thermoelectric principles and conductive polymer characteristics, followed by the recent progress in their application in flexible and wearable thermoelectric devices. We also evaluate new advances in manufacturing hybrids of π-conjugated polymers with other polymers, inorganic materials, or carbon nanostructures, and their applications in body energy harvesting and smart cooling. Graphical abstract: Image 1 Highlights: A review assessing state of the art flexible and wearable heat-to-electricity energy convertors. Categories and characteristics of thermoelectric conductive polymers and their nano-hybrids. A physics, chemistry and technology framework for thermoelectric body heat harvesting research. Outlook on the organic/polymer field challenges to upscale thermoelectric energy convertors.